1989
DOI: 10.1128/jvi.63.5.2317-2324.1989
|View full text |Cite
|
Sign up to set email alerts
|

Two blocks in Moloney murine leukemia virus expression in undifferentiated F9 embryonal carcinoma cells as determined by transient expression assays

Abstract: Transient expression assays were used to investigate the restriction of Moloney murine leukemia virus (MoMuLV) expression in undifferentiated mouse F9 embryonal carcinoma (EC) cells. We previously reported that the MoMuLV long terminal repeat (LTR) is inactive in undifferentiated F9EC cells due to inactivity of the tandemly repeated MoMuLV transcriptional enhancers. Others suggested that the inactivity was due to the presence of negative regulatory elements that interact with the MoMuLV tandem repeats. Two het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
40
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 36 publications
0
40
0
Order By: Relevance
“…The main conclusion from these experiments is that the RBS/NRE, which has been shown to mediate the silencing of MoMuLV in undifferentiated EC cells (1,6,(17)(18)(19)(20)29), is also involved in the repression of MoMuLV template expression in early mouse embryos. Our observation that the B2 point mutation in the RBS/NRE relieves the block to expression from an active promoter in two-cell embryos as it does in EC cells strongly argues for identical mechanisms of repression in both cases.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…The main conclusion from these experiments is that the RBS/NRE, which has been shown to mediate the silencing of MoMuLV in undifferentiated EC cells (1,6,(17)(18)(19)(20)29), is also involved in the repression of MoMuLV template expression in early mouse embryos. Our observation that the B2 point mutation in the RBS/NRE relieves the block to expression from an active promoter in two-cell embryos as it does in EC cells strongly argues for identical mechanisms of repression in both cases.…”
mentioning
confidence: 93%
“…A restriction on productive infection is also observed in undifferentiated murine embryonal carcinoma (EC) cells and in embryonal stem cell lines. Detailed studies have shown that the block to transcription from the MoMuLV long terminal repeat (LTR) in these cells is the effect of two independent mechanisms: (i) the inability of enhancer elements to activate transcription (16), imputed in part to the absence of the cognate transcription factors (24), and (ii) the presence of cisacting negatively regulating sequences (1,6,8,17,18,26). A point mutation in the 5Ј noncoding region, initially found in the B2 provirus, was shown to permit virus expression in F9 EC cells (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The NCR sequence has been shown to bind a cellular factor, thereby mediating transcriptional repression (13). Another well-defined inhibitory element is located at the primer binding site (PBS) of the MoMuLV leader region (12,24,39,42). The sequence from the MoMuLV PBS acts by binding a cellular factor which inhibits RNA transcription (22,25,30).…”
mentioning
confidence: 99%
“…Especially, Moloney murine leukemia virus (MoMLV)-based retroviral vectors that have been most commonly used in gene therapy fields are very susceptible to de novo methylation in immature cells such as embryonic stem (ES) cells or embryonal carcinoma (EC) as well as somatic hematopoietic stem cells (Linney et al 1984;Tsukiyama et al 1989), resulting in shut off/silencing of the transgene expression in vivo. Intensive molecular analysis has revealed that the shut off/silencing of the transgene expression often observed in MoMLV-infected cells is attributed to the viral structure characterized by the longterminal repeat (LTR) with the negative control region (NCR) and the primer binding site that contain target sequences for the repressor binding protein and the negative transcriptional factors, respectively (Feuer et al 1989;Flanagan et al 1989). The presence of fetal calf serum (FSC) in the retroviral suspensions is also a critical problem because it prematurely induces the differentiation of neurospheres into neurons that have little, if any, proliferative activity.…”
mentioning
confidence: 99%